1999
DOI: 10.1002/hep.510290616
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis C virus-related cirrhosis: A randomized, controlled trial of interferon alfa-2b versus no treatment

Abstract: To examine the effects of interferon (IFN) therapy on clinical, biochemical, and histological features in patients with compensated hepatitis C virus (HCV)-related cirrhosis, we have conducted a randomized, controlled trial of IFN therapy versus observation. Eight centers included a total of 99 patients with biopsy-proven cirrhosis. IFN-␣2b, 3 million units three times per week, or no antiviral therapy was given for 48 weeks. Twenty-three patients dropped out. End-of-treatment biochemical response was not obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(163 citation statements)
references
References 28 publications
(48 reference statements)
5
151
0
7
Order By: Relevance
“…However, the rates of SVR in our study is consistent with those obtained in similar patients using this schedule of treatment, 36 and might be justified by the sole inclusion of a cohort of patients with "early" stage of cirrhosis with moderate of portal hypertension and, of a high proportion of patients infected by "easy-to-treat" genotype 2. 37 In conclusion, our data show that, in patients with HCV-related histologically proven cirrhosis, the achievement of a SVR following IFN treatment was associated with a reduction in liver-related mortality and with a lower risk of liver-related complications and occurrence of HCC.…”
Section: Discussionsupporting
confidence: 88%
“…However, the rates of SVR in our study is consistent with those obtained in similar patients using this schedule of treatment, 36 and might be justified by the sole inclusion of a cohort of patients with "early" stage of cirrhosis with moderate of portal hypertension and, of a high proportion of patients infected by "easy-to-treat" genotype 2. 37 In conclusion, our data show that, in patients with HCV-related histologically proven cirrhosis, the achievement of a SVR following IFN treatment was associated with a reduction in liver-related mortality and with a lower risk of liver-related complications and occurrence of HCC.…”
Section: Discussionsupporting
confidence: 88%
“…61 The rest of the studies, mostly retrospective and nonrandomized, suggested a moderate decrease in the risk for HCC among HCVinfected patients treated with interferon. 54,8,[62][63][64][65][66][67][68][69] In general, the reported preventive effect of interferon alfa therapy was less marked in European studies than in studies from Japan. The benefit was better appreciated in patients with sustained response than nonresponders.…”
Section: Hcc In Hcv-related Cirrhosismentioning
confidence: 99%
“…In 1995, a small randomized controlled trial (RCT) showed a decrease in the incidence of HCC in patients with HCV cirrhosis compared with untreated controls [8]. In the wake of this study, several controlled trials [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were performed. These studies, often assessed retrospectively, collected cohorts of a relatively small size and having a marked degree of heterogeneity, making it difficult to assess the actual level of benefit obtained by IFN treatment.…”
Section: Secondary Preventionmentioning
confidence: 99%